Incidence of omental metastasis in uterine serous carcinoma: study protocol for a systematic review and meta-analysis. Issue 1 (17th January 2021) - Hu, Cui; Zhang, Lin-Lin; Cheng, Yu; Xue, Fei-Xue; Jia, Ya; Zhao-Juan, Qin; Yi, Du; Qian-Wen, Zhang; Yue-Dong, He; Ai, Zheng; Xu, Yu
Abstract : Introduction: Uterine serous carcinoma accounts for only about 10% of all endometrial cancers but this subtype is the most common amongst non-endometrioid endometrium cancers and contributes to more than half of recurrence and deaths attributed to endometrial cancers. A more extensive surgical staging and adjuvant therapies for uterine serous carcinoma are recommended by many guidelines. However, guidelines vary on recommendations for the methods that should be used for omentum assessment in uterine serous carcinoma and the previously reported incidence of omental metastasis in uterine serous carcinoma had a wide range because of the heterogeneity among these studies. As far as we know, there are no systematic review and meta-analysis available on this topic. The aim of our proposed study is to statistically synthesise the data examining the incidence of omental metastasis in uterine serous carcinoma. Methods and analysis: Systematic searches of three databases (PubMed, Embase and Web of Science) will be performed using prespecified search strategies. We will include original studies that reported incidence of omental metastasis in uterine serous carcinoma and are published before 30 August 2020. Our different investigators will independently conduct the eligible study selection, assess the quality of included studies and extract the needed data. If appropriate, the relevant data will be pooled through a random-effect or fixed-effect meta-analysis based on the heterogeneity among included studies. We will evaluate the overall quality of evidence using appropriate methods. Ethics and dissemination: This proposed study will be based on published data, and thus, there is no requirement for ethics approval. We aim to publish the results of this study in a peer-reviewed journal with good visibility for the fields of gynaecology and gynecologic oncology. PROSPERO registration number: CRD42020200891.